Pulmonary nocardiosis associated with Cushing’s disease: a case report - Mylonas, Charalampos C.; Gomatou, Georgia; Asimakopoulou, Athina; Masaoutis, Christos; Kyriakopoulos, George; Kopelia, Maria; Syrigos, Konstantinos; Poulakou, Garyphallia (Monaldi Archives for Chest Disease, 2019)
Nocardia spp. is a genus of Gram-positive bacteria which can cause cutaneous, pleuropulmonary, or disseminated disease. The latter two forms are encountered in immunocompromised patients, with prolonged usage of corticosteroids being a well-recognized risk factor. However, endogenous Cushingâ€™s syndrome is less frequently associated with nocardiosis. We report on a 40-year-old woman who presented for further workup of abnormal findings in the chest computed tomography (three lung nodules, one of which being cavitary). She underwent trans-thoracic fine-needle lung aspiration of the cavitary nodule, which led to the diagnosis of lung nocardiosis. Moreover, the identification of cushingoid features from the history and clinical examination initiated further investigation with hormonal laboratory assessment and bilateral inferior petrosal sinus sampling which established the diagnosis of pituitary adrenocorticotropic hormone (ACTH) hypersecretion (Cushingâ€™s disease). We conclude that pulmonary nocardiosis can be an opportunistic infection as well as a presenting manifestation of Cushing’s disease.